3
$\begingroup$

I wonder the convergence of the series $$\sum_{n=1}^\infty (-1)^n {(2n)!\over 4^nn!(n+1)!}.$$

We can derive that the general term is equal to $$(-1)^n \times {1\over2} \times {3 \over 4} \times \cdots \times {2n-1 \over 2n} \times {1 \over n+1}.$$

We can easily see that the series derived by taking absolute value is monotone decreasing and converges to $0$, so that the original series converges, by Alternating Series Test. Then, does it converges absolutely/conditionally? I feel like it converges absolutely, since ${1\over n}$ is somewhat the threshold of convergence/divergence and the term ${1\over2} \times {3 \over 4} \times \cdots \times {2n-1 \over 2n}$ is sufficiently small that it will make the series converge, but I have no idea how to deal with it.

$\endgroup$
  • $\begingroup$ What have you tried? Have you attempted to apply any of the usual tests for convergence (e.g. the ratio test, the root test, etc.)? $\endgroup$ – Xander Henderson Nov 22 '17 at 16:30
  • $\begingroup$ I tried both ratio test and root test, but did not work. maybe I should try to apply abel/dirichlet test?? they are the most powerful tests that the textbook serves $\endgroup$ – Jeongmin Park Nov 22 '17 at 16:32
1
$\begingroup$

Yes, it converges absolutely. By using Stirling approximation $n!=\sqrt{2\pi n}(n/e)^n$ (see also the approximation of the central binomial coefficient here), it follows that $${(2n)!\over 4^nn!(n+1)!}=\frac{1}{n+1}\cdot\frac{\binom{2n}{n}}{4^n}\sim\frac{1}{n}\cdot\frac{1}{\sqrt{\pi n}}\sim\frac{1}{\sqrt{\pi}n^{3/2}}$$ and the series $\sum 1/n^{3/2}$ is convergent because $3/2>1$.

$\endgroup$
1
$\begingroup$

You may notice that the extended binomial theorem gives (for any $x\in(-1,1)$): $$ \frac{1}{\sqrt{1-x}}=(1-x)^{-1/2} = \sum_{n\geq 0}\binom{-\tfrac{1}{2}}{n}(-1)^n x^n =\sum_{n\geq 0}\frac{\binom{2n}{n}}{4^n}x^n$$ hence by performing $\int_{0}^{z}(\ldots)\,dx $, we get: $$2-2\sqrt{1-z} = \sum_{n\geq 0}\frac{\binom{2n}{n}}{(n+1)4^n}\,z^{n+1} $$ then by dividing both sides by $z$ and replacing $z$ with $-x$: $$ \frac{2}{1+\sqrt{1+x}} = \sum_{n\geq 0}\frac{\binom{2n}{n}(-1)^n}{(n+1)4^n}\,x^n $$ and subtracting $1$ to both sides: $$ \frac{1-\sqrt{1+x}}{1+\sqrt{1+x}} = \sum_{n\geq 1}\frac{\binom{2n}{n}(-1)^n}{(n+1)4^n}\,x^n. $$ Since

$$\frac{1}{4^n}\binom{2n}{n}=\frac{2}{\pi}\int_{0}^{\pi/2}\cos^{2n}(\theta)\,d\theta \leq \frac{2}{\pi}\int_{0}^{\pi/2}e^{-n\theta^2}\,d\theta\leq \frac{2}{\pi}\int_{0}^{+\infty}e^{-n\theta^2}\,d\theta = \frac{1}{\sqrt{\pi n}}$$ the previous series evaluated at $x=1$ is absolutely convergent and $$ \sum_{n\geq 1}\frac{\binom{2n}{n}(-1)^n}{(n+1)4^n} = \frac{1-\sqrt{2}}{1+\sqrt{2}} = \color{red}{2\sqrt{2}-3}.$$

$\endgroup$
0
$\begingroup$

With Gauss' test: $$\Big|\dfrac{a_{n+1}}{a_n}\Big|=\dfrac{2n+1}{2n+4}=1-\dfrac{\frac32}{n}+\dfrac{\frac{3n}{n+2}}{n^2}$$ and $\dfrac{3n}{n+2}<3$, so with $p=\dfrac32>1$ the series is converges absolutely.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.